Study on the uniformity of high concentration photovoltaic system with array algorithm - Gong, Jinghu; Wang, Chenglong; Gong, Chenyang; Liang, Fei; Ma, Jun (Solar energy, 2017)
•In this paper, a new algorithm is proposed about the plane mirror array, which is used to study the uniformity of the energy flux density on the surface of the receiver, the simulation results show that the uniformity is more than 99%, and the experimental result (96.907%) is in agreement with the simulation results.•In the case of the theoretical concentration ratio C is unchanged, the effective area of the photoelectric conversion is unchanged with the increase of the focal length.•In the case of theoretical concentration ratio C and DNI are unchanged, the relationship of the maximum irradiance Emax with focal length f is Emax=a+b ln(f-c), and the relationship of the average irradiance Eave with focal length f is also Eave=a+b ln(f-c). The uniformity of the receiver surface energy flux density in the reflective high-power concentration photovoltaic system can affect the photoelectric conversion efficiency of the photovoltaic cell, and even cause the “hot spot” to damage it. In this paper, the plane mirror array algorithm is used to design a reflective high-power condenser, and TRACEPRO is used to numerical simulation study the uniformity of receiver surface energy flux density. The results show that the uniformity is greater than 99%, the experimental result (96.907%) is in agreement with the simulation results. In addition, the relationships of the effective area of the photoelectric conversion, the average irradiance, the maximum irradiance and the focal length are studied, and in the case of theoretical concentration ratio C is unchanged, the effective area of the photoelectric conversion is unchanged, the relationship of the maximum irradiance Emax with the focal length f is Emax=a+b ln(f-c), and the relationship of the average irradiance Eave with focal length f is also Eave=a+b ln(f-c).